Complex history of the amphibian-killing chytrid fungus revealed with genome resequencing data - Rosenblum, Erica Bree (National Academy of Sciences, 2013)
Understanding the evolutionary history of microbial pathogens is critical for mitigating the impacts of emerging infectious diseases on economically and ecologically important host species. We used a genome resequencing approach to resolve the evolutionary history of an important microbial pathogen, the chytrid Batrachochytrium dendrobatidis (Bd), which has been implicated in amphibian declines worldwide. We sequenced the genomes of 29 isolates of Bd from around the world, with an emphasis on North, Central, and South America because of the devastating effect that Bd has had on amphibian populations in the New World. We found a substantial amount of evolutionary complexity in Bd with deep phylogenetic diversity that predates observed global amphibian declines. By investigating the entire genome, we found that even the most recently evolved Bd clade (termed the global panzootic lineage) contained more genetic variation than previously reported. We also found dramatic differences among isolates and among genomic regions in chromosomal copy number and patterns of heterozygosity, suggesting complex and heterogeneous genome dynamics. Finally, we report evidence for selection acting on the Bd genome, supporting the hypothesis that protease genes are important in evolutionary transitions in this group. Bd is considered an emerging pathogen because of its recent effects on amphibians, but our data indicate that it has a complex evolutionary history that predates recent disease outbreaks. Therefore, it is important to consider the contemporary effects of Bd in a broader evolutionary context and identify specific mechanisms that may have led to shifts in virulence in this system.